Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/aas.13235
|View full text |Cite
|
Sign up to set email alerts
|

Association between perioperative hyperoxia and cerebrovascular complications after laparotomy—A post‐hoc follow‐up study

Abstract: Stroke or TCI did not seem related to perioperative inspiratory oxygen fraction. Due to few events, this study cannot exclude that perioperative hyperoxia increases risk of mortality, stroke, or TCI after abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Hyperoxia increases ROS levels that inactivate NO thereby resulting in systemic, coronary, and cerebral vasoconstriction. 23,24 This effect is very crucial during the reperfusion period in patients with AIS treated by endovascular thrombectomy to avoid excess production of ROS. Of note, 100% inspiratory oxygen results in reducing mean cerebral blood flow by 27% in young healthy adults and 16% mean reduction in an older subgroup in interventional magnetic resonance imaging study.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia increases ROS levels that inactivate NO thereby resulting in systemic, coronary, and cerebral vasoconstriction. 23,24 This effect is very crucial during the reperfusion period in patients with AIS treated by endovascular thrombectomy to avoid excess production of ROS. Of note, 100% inspiratory oxygen results in reducing mean cerebral blood flow by 27% in young healthy adults and 16% mean reduction in an older subgroup in interventional magnetic resonance imaging study.…”
Section: Discussionmentioning
confidence: 99%
“…However, when regarding cardiovascular AE, a meta-analysis of three studies showed no signal of increased ratios of these AE in patients receiving high FiO 2 [12]. Data on the incidence of stroke and transitory cerebral ischemia are available from only one trial; no increased incidence was found in patients who received high instead of normal FiO 2 [31].…”
Section: Cardiovascular and Cerebrovascular Complicationsmentioning
confidence: 98%
“…The reduction of the cerebral flow and neurotoxicity were described after hyperoxia exposure [ 39 ]. The clinical relevance of these effects was not clearly established, as a recent post hoc follow-up study including abdominal surgical patients exposed to 30% vs. 80% oxygen, found no difference in the incidence of stroke or transient cerebral ischemia [ 40 ].…”
Section: Hyperoxia Effects On Surgical Cancer Patients—clinical and Experimental Datamentioning
confidence: 99%